1975
DOI: 10.1161/01.str.6.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Studies on the Intracerebral and Retinal Arteries in Cerebrovascular and Noncerebrovascular Diseases

Abstract: Abstract• Histological examinations of the intracerebral and retinal arteries were performed in patients who had cerebrovascular disease and in those cases who did not. Fibrinoid degeneration, fibrous nodule, and splitting, which are most frequently found in putamen, thalamus and pons, are thought to be the main changes in cerebral hemorrhage and infarction. Fibrous and fibro-hyalinoid thickenings of the retinal arteries were found mainly in the neighboring region of the optic disk, which reflects the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 11 publications
2
78
0
4
Order By: Relevance
“…Pathological studies have shown a close correlation between cerebral and retinal vascular findings. 32 With advance in retinal photography, retinal vascular imaging has been proposed to be a noninvasive tool to assess the cerebral microvasculature objectively and reliably for better understanding of the pathophysiological processes involved in cerebral small vessel disease. 4,33 To our best knowledge, this is the first study to examine the relationship between retinal microvascular abnormalities and the risk of stroke in an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological studies have shown a close correlation between cerebral and retinal vascular findings. 32 With advance in retinal photography, retinal vascular imaging has been proposed to be a noninvasive tool to assess the cerebral microvasculature objectively and reliably for better understanding of the pathophysiological processes involved in cerebral small vessel disease. 4,33 To our best knowledge, this is the first study to examine the relationship between retinal microvascular abnormalities and the risk of stroke in an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which the structure and function of the retinal microvasculature mirrors the cerebral microvasculature, and microvascular beds elsewhere, is not clear. Histopathologic studies suggest that retinal vascular signs 16 are closely related to pathological microvascular changes in other organs (eg, hypertensive arteriolar changes in the brain 17 and myocardium 18 ). Other studies demonstrate that persons with lacunar stroke have functional alterations in the retinal vasculature 19 including reduced retinal arteriolarvenule passage time.…”
Section: Homology Between Retinal Microvasculature and Other Microvasmentioning
confidence: 99%
“…6,10 -13 The retinal microvasculature shares similar anatomic, physiological, and embryological characteristics with the cerebral vasculature. 14,15 Quantitative measurement of retinal microvascular changes is now possible using reproducible, computer-assisted methods to examine retinal photographs. 16 Population-based studies further showed that subtle retinal vascular caliber changes (particularly narrower arterioles and wider venules) independently predicted stroke and stroke death.…”
mentioning
confidence: 99%